Pavement marking materials and markers testing the relationship between retroreflectivity and safety. - Bahar, Geni Brafman; National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board (Washington, D.C. Transportation Research Board, 2006)
"This digest summarizes key findings from NCHRP Project 17-28, "Pavement marking materials and markers : safety impact and cost-effectiveness" conducted by iTRANS Consulting, Ltd. The digest is an abridgement of portions of the project final report authored by the principal investigator, Geni Bahar ... [et al.]."
Caption title.
"August 2006."
Includes bibliographical references (p. 6).
Also issued online.
Keywords: Road markings -- Materials -- Testing; Reflectance -- Testing; Traffic safety